Depletion of Biological Assets: Treatment and Impact on Financial Statements - Ardiana, Meta; Agustina, Rachma (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This study aims to analyze the treatment of depletion or decrease in the value of biological assets and its impact on financial reports on Wibowo Farm farms in Blitar. Data collection techniques using literature study, observation, interviews, and documentation. I was checking the validity of the data through participation extension, observation persistence, and data triangulation. The result of the study was Wibowo Farm has acknowledged that there is depreciation or depletion of non-productive biological assets based on the productive value of these biological assets, if there is a death, the biological assets have also been recognized as depreciation but have not been presented in detail in the balance sheet financial statements, this is relevant to PSAK 69 which requires a calculation of impairment in the economic value of biological assets. For presentation in the financial statements of biological assets, it is reported in the balance sheet financial statements in detail on the biological assets produced. Wibowo Farm's livestock only recognizes the advantages and disadvantages when ignoring biological assets. This difference, of course, makes financial reports less reliable and relevant